PEMASARAN DURIAN DI PASAR INDUK KRAMAT JATI - Sabrina, Sabrina; Winandi, Ratna; Rachmina, Dwi (Forum Agribisnis, 2013)
This study aimed to analize the marketing institution, market structure and marketing efficiency of local and imported durio in pasar induk kramat jati. Marketing institution analysis covered marketing channel and marketing function analysis, while operational efficiency was measured by margin analysis and benefit-cost ratio analysis. A snowball sampling that was started from a fruit stall in pasar kramat jati revealed that the local durio comes from Palembang, Lampung, and Bengkulu, while the imported durio was imported from ThÃ iland by the importeer in Tanjung Priok. Both local durioand imported durio was distributed to the consumer by the fruit wholeseller and retailer. The exchanging function, physical function and facilitating function are done by all of the durio marketing institution. The durio market structure is vary, perfect competition market, oligopoly and monopolistic market for local durio and oligopoly, monopoly and monopolistic for imported durio. Although the marketing efficiency of local and imported durio quite the same due to the similarity of its benefit-cost ratio, but the local durio cannot beat the imported durio in term of its quality.